Review—Contemporary Progresses in Carbon-Based Electrode Material in Li-S Batteries. Issue 2 (1st February 2022) - Chadha, Utkarsh; Bhardwaj, Preetam; Padmanaban, Sanjeevikumar; Suneel, Reyna Michelle; Milton, Kevin; Subair, Neha; Pandey, Akshat; Khanna, Mayank; Srivastava, Divyansh; Mathew, Rhea Mary; Selvaraj, Senthil Kumaran; Banavoth, Murali; et al.
Abstract : Lithium-sulfur batteries are among the rising rechargeable batteries due to their high energy density, theoretical capacity, and low cost. However, their large-scale application is delayed by several challenges, such as degradation due to polysulfide dissolution, low conductivity, and other restricting factors. Li-S batteries have undergone decades of development aimed at improving battery performance by altering the electrode material to overcome these challenges. In the meantime, due to the depletion of fossil fuels and growing energy demand, the need for changes in processes to improve battery performance is now more urgent than ever. Carbon-based materials like conducting polymers, carbon nanotubes, Graphene, and activated Carbon have gained extensive attention due to their low cost, easy availability, good cycling stability, and exceptional electrical, thermal, and mechanical properties. Here, we summarize recent progress in carbon-based electrode material in Li-S batteries, the development of electrolytes, and progress in adopting lithium-sulfur batteries as flexible devices. Furthermore, a comparison of Li-S batteries based on similar parameters with its rechargeable battery competitors is discussed and a comparison with other non-carbon-based electrodes used in the lithium-sulfur battery is also examined. Finally, a general conclusion and future directions are given.